Biometry, length-weight and length-length relationships of flathead sillago Sillaginopsis panijus (Hamilton, 1822) (Perciformes: Sillaginidae) from the north-western Bay of Bengal - Pradhan, Suraj Kumar; Roul, Subal Kumar; Ghosh, Shubhadeep; Tripathy, Pritam; Jaiswar, A. K.; Bhusan, Sashi; Nayak, B. B. (Indian Journal of Fisheries, 2020)
Biometry, length-weight relationships (LWRs) and length-length relationships (LLRs) of Sillaginopsis panijus (Hamilton, 1822) were investigated in the Indian coast of north-western Bay of Bengal. Altogether 622 specimens were collected between August 2018 and September 2019 from landings by trawls (30-35 mm mesh size), gillnets (15-55 mm mesh size) and shore seines (7-15 mm bag mesh size). The total length and weight of the specimens ranged from 7.8-40.3 cm and 2.9-506 g, respectively. The LWR established was W=0.0048 L3.059 for males, W=0.0032 L3.185 for females and W=0.0047 L3.0645 for indeterminates, indicating positive allometric growth pattern. All the LWRs were highly significant (p<0.001, r2â‰¥0.977). The highest coefficient of correlation (r) was observed for total length against fork length (0.999) and lowest for head length against eye diameter (0.951). The fin formula was expressed as D1 X, D2 I + 24-28, P 17-22, V I + 5, A II + 25-27, GR 2-3/6-9. The study provides the first detailed account of the biometric relationships of S. panijus in the north-western Bay of Bengal, which can be used as baseline information for subsequent biological and population based studies in the region. Â Keywords: Biometry, Flat head sillago, Length-weight relationship, North-western Bay of Bengal, Sillaginopsis panijus.